2016
DOI: 10.1186/s13717-016-0064-2
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanisms on inhibition of photosynthesis in Kandelia obovata due to extreme cold events under climate change

Abstract: Introduction: Mangroves that grow at the latitudinal extremes of their distribution are susceptible to extreme cold events. Successive enhancement of low temperature stress (seLTS) is a typical characteristic of extreme cold events. Low temperature stress can inhibit mangrove photosynthesis, which often inhibits the growth and development of mangroves. However, the possible reasons for impairment to photosynthesis of mangroves due to extreme cold events remain unclear. Methods: Kandelia obovata seedlings in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Mangrove tree species that grow in tropical and subtropical intertidal zones are poorly adapted to chilling (Gu et al ., 2021). In subtropical regions, mangroves experience seasonal chilling as well as occasional extreme cold waves, and only chilling‐tolerant species and genotypes can migrate poleward in response to global warming (Salem & Mercer, 2012; Zheng et al ., 2016; Saenger et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mangrove tree species that grow in tropical and subtropical intertidal zones are poorly adapted to chilling (Gu et al ., 2021). In subtropical regions, mangroves experience seasonal chilling as well as occasional extreme cold waves, and only chilling‐tolerant species and genotypes can migrate poleward in response to global warming (Salem & Mercer, 2012; Zheng et al ., 2016; Saenger et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have examined the chilling effect on the photosynthesis of warm‐climate plants, including mangroves species (Zheng et al ., 2016; Chen et al ., 2017). However, there are no studies to document alterations in leaf P fractions and their correlations with photochemistry efficiency, nighttime respiration, and relative gene expression under chilling stress.…”
Section: Introductionmentioning
confidence: 99%
“…Chilling stress is complex and adversely affects the morphological, physio-biochemical, and molecular processes in plants, thus it reduces their growth and development (Allen and Ort 2001, Elsheery et al 2020, Li et al 2021, Mathur et al 2021. Earlier studies have revealed the influence of chilling in combination with varying incident light intensities on photosynthesis and photoprotection mechanisms of plants, including diverse tropical tree species (Someralo and Krause 1990, Barth and Krause 1999, Elsheery et al 2008, Huang et al 2010aZheng et al 2016, Yang et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have been conducted to understand the photoprotection mechanisms and sensitivity of photosystems in tropical tree species found in the marginal tropics of China (Huang et al 2010a,b;Zheng et al 2016, Yang et al 2017. However, such studies were conducted at the seedling stage with artificial chilling treatments for a short duration (hours), and their results demonstrate the activation of photoprotection mechanisms, i.e., CEF and NPQ.…”
Section: Introductionmentioning
confidence: 99%
“…Kandelia obovata, a mangrove species widely distributed in extremely saline environments in eastern Asia [ 7 ]. Learning from such halophytes and tailoring the traits associated with high salinity tolerance may build a foundation for salt tolerance in glycophytes.…”
Section: Introductionmentioning
confidence: 99%